2019
DOI: 10.1063/1.5091797
|View full text |Cite
|
Sign up to set email alerts
|

The boundary layer flow induced above the torsional motion of a disk

Abstract: The boundary layer flow above a disk in torsional motion with azimuthal velocity proportional to r m is investigated for all values of m ≥ 1; here r is the radial coordinate measured from the center of the disk. The resulting flow is a fully three-dimensional exact solution to the steady, axisymmetric boundary layer equations in the form of similarity solutions. We compute wall shear stresses in the radial and azimuthal directions as a function of the torsional exponent m, as well as the flow induced in the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Thus, it is concluded that penetration depth is higher for small values of Re. Furthermore, the axial flow induced here is similar to the one discussed by the Tetervin-Akatnov-Glauert wall jet (named as TAG, by [33]). In figure 3(c), the azimuthal velocity profile ˜( ) h g is presented for   0 Re 10 .…”
Section: Discussion and Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Thus, it is concluded that penetration depth is higher for small values of Re. Furthermore, the axial flow induced here is similar to the one discussed by the Tetervin-Akatnov-Glauert wall jet (named as TAG, by [33]). In figure 3(c), the azimuthal velocity profile ˜( ) h g is presented for   0 Re 10 .…”
Section: Discussion and Resultssupporting
confidence: 65%
“…Mastroberardino and Siddique [32] employed the shooting method and studied the stretching and permeable cylinder with MHD flow. Turner and Weidman [33] inquired on the flow rotating about its center, caused above a twisting disk. Rivero et al [34] found the exact solutions for the Stokes second problem for a cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the study of the radial stagnation flow of micropolar fluid over a twisting cylinder is presented. The initial flow is obtained by Weidman [4] in which he considered viscous flow. The impact of the micropolar fluid parameters on the flow characteristics has been studied under the concentration of microelements.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that in the meridional plane, the axial pressure gradient persuades a weak transverse flow. Turner and Weidman [4] studied the boundary layer flow persuaded over the torsional motion of the disk. They found that the induced radial velocity profiles have a wall jet structure, furthermore, as the torsional exponent increases, the radial and azimuthal velocity components are restricted near the surface of the disk.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Reddy et al [24] considered Eyring-Powell nanoliquid to investigate the chemical reaction effects on a stretchable cylinder numerically. In recent years, different researchers utilized the chemical reaction impacts for different geometries [25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%